Inflation Dynamics in FYR Macedonia - Shamloo, Maral (IMF Working Papers; Working Paper, 2011)
In this paper we study the dynamics of inflation in Macedonia, provide three forecasting tools and draw some policy conclusions from the quantitative results. We explore three forecasting methods for inflation. We use a Dynamic Factor Model (DFM) for short-term, monthly forecasting. We also develop two quarterly models: A Vector Error Correction Model (VECM), and a New Keynesian Phillips Curve (NKPC) for a more structural model of inflation. The NKPC shows a significant effect of output gap and inflation expectations on current inflation, confirming that the expectations channel of monetary transmission mechanism is strong. In terms of forecast-error variance, we show that all three models do very well in one-period ahead forecasting.